Parochodaeus Bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia Gentilii (Martínez) (Coleoptera: Scarabaeidae), Two Species Newly Discovered in Chile - Fierro-Tapia, C (Magnolia Press, 2019)
[No abstract available]